54. DISEASE PATTERN OF IN-PATIENTS AT DUC GIANG GENERAL HOSPITAL, HANOI IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the disease pattern of in-patients at Duc Giang General Hospital, Hanoi in 2024.Materials and methods: A cross-sectional descriptive study, taking all in-patients at Duc Giang General Hospital from January 1, 2024 to December 31, 2024.Results: The total number of in-patients at Duc Giang General Hospital in 2024 was 49,602. Of which, women accounted for 51.8%, the proportion of patients with health insurance was 92.3%. The average age of patients was 45.4 ± 24.8 years old; the age group 60–79 had the highest proportion (35.7%). Non-communicable diseases accounted for the majority (84.9%), the most common being respiratory, musculoskeletal and digestive diseases.The proportions of hypertension, diabetes, spinal pathology and vestibular dysfunction were higher in female patients; pneumonia, kidney and ureteral stones were higher in male patients (p 0.05). Some diseases changed over time, with pneumonia being most common in January, hypertension in March and cerebral stroke in July.Conclusion: In-patients treated at Duc Giang General Hospital, Hanoi in 2024 are mostly in the group of non-communicable diseases. There are differences in disease pattern by gender and time of year. This result contributes to the orientation of building management, prevention and medical examination and treatment programs.
Keywords: Disease pattern; in-patient; non-communicable diseases.